(untitled) (Journal of Parents and Teachers, 1996)
Educational and cultural activities for the whole family are highlighted, such as visits to museums and theater performances. In addition, children’s books on science and ecology are recommended, encouraging hands-on learning. Discussion and exchange of ideas are considered essential in the educational process.